Regulatory arbitrage and the efficiency of banking regulation - Boyer, Pierre C.; Kempf, Hubert (Journal of Financial Intermediation, 2020)
We study the efficiency of banking regulation under financial integration. Banks freely choose the jurisdiction where to locate their activities and have private information about their efficiency level. Regulators non-cooperatively offer any regulatory contract that satisfies information and participation constraints of banks. We show that the unique Nash equilibrium of the regulatory game is a simple pooling contract: financial integration is characterized by the inability for regulators to discriminate between banks with different efficiency levels. This result is driven by the endogenous restriction caused by regulatory arbitrage on the capacity of regulators to use several regulatory instruments.